COASTAL AND MARINE BIODIVERSITY EXPERT GROUP CONSULTATION WORKSHOP - Cindy, Peter (IBEC, 2020)
In collaboration with WWF-Malaysia and Universiti Malaya (UM), the Malaysian Society of Marine Sciences (MSMS) organized an expert group consultation workshop from 3rd to 5th of March 2020 at Universiti Malaya, Kuala Lumpur. The experts consisted of 28 lecturers and postgraduate students from various public and private universities as well as staff of WWF-Malaysia. Ms Cindy Peter (IBEC) and Dr Aazani Mujahid (FRST) were the invited representatives from UNIMAS as marine mammals and oceanography researchers.